Life of Pi a novel - Martel, Yann 1963- (Great Britain Alfred A. Knopf, 2001)
WINNER OF THE 2002 BOOKER PRIZE After the tragic sinking of a cargo ship, one solitary lifeboat remains bobbing on the wild, blue Pacific. The crew of the surviving vessel consists of a hyena, a zebra (with a broken leg), a female orang-utan, a 450-pound Royal Bengal tiger and Pi -- a 16-year-old Indian boy. The scene is set for one of the most extraordinary pieces of literary fiction of recent years.
Keywords: Tiger; Religion; Überleben; Shipwreck victims -- India